2014
DOI: 10.1159/000380951
|View full text |Cite
|
Sign up to set email alerts
|

Gene-Gene Interplay and Gene-Diet Interactions Involving the <b><i>MTNR1B </i></b>rs10830963 Variant with Body Weight Loss

Abstract: Background/Aims: Investigation of the genetic makeup may facilitate the implementation of more personalized nutritional interventions. The aims were to examine whether the rs10830963 MTNR1B polymorphism affects weight loss in response to a hypocaloric diet and to find potential gene-gene interplays and gene-diet interactions. Methods: 167 subjects enrolled in a personalized nutritional intervention for weight loss (3-6 weeks) were examined for anthropometric measurements, dietary habits and physical activity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 50 publications
1
14
1
Order By: Relevance
“…However, a limited number of studies have analyzed the association between melatonin-related genes and body weight loss. In contrast to 2 previous studies, our group observed an association between the rs10830963 genetic variant near melatonin receptor 1B (MTNR1B) and body weight loss in a shortterm weight loss intervention in women (22)(23)(24). On the other hand, the rs12452844 polymorphism of the aralkylamine N-acetyltransferase (AANAT) gene has been associated with 1 y weight change (25).…”
Section: Nutrigeneticscontrasting
confidence: 80%
“…However, a limited number of studies have analyzed the association between melatonin-related genes and body weight loss. In contrast to 2 previous studies, our group observed an association between the rs10830963 genetic variant near melatonin receptor 1B (MTNR1B) and body weight loss in a shortterm weight loss intervention in women (22)(23)(24). On the other hand, the rs12452844 polymorphism of the aralkylamine N-acetyltransferase (AANAT) gene has been associated with 1 y weight change (25).…”
Section: Nutrigeneticscontrasting
confidence: 80%
“…Even if a possible interaction among ACE , MC4R , FTO and PPARG genes can be inferred by GWASs, which supported their relation with obesity and overweight, previous investigations did not test the presence of synergistic effects using a targeted approach. However, it should be mentioned that several studies have been conducted on this topic; a longitudinal study from Bouwman et al reported that adult men carrying FTO rs9939609 T/T genotype + ACE rs4646994‐D allele were protected against weight gain over a 10‐year period; Lazopoulou et al showed a cumulative effect of the presence of FTO rs9939609‐A allele and MC4R rs17782313‐C allele on childhood obesity in a Greek population; Goni et al showed that carrying unfavorable genotypes at both FTO rs9939609 and MC4R rs17782313 loci can influence weight loss in response to a hypocaloric diet; Carlos et al failed to prove the interaction of FTO rs9939609 and PPARG rs1801282 with obesity in Portuguese women; Passaro et al demonstrated a gene–gene interaction between PPARG rs1801282 and ACE rs4646994 on BMI and fat mass.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the rs10830963 associates with the outcome of an intervention that targets weight loss [10]. The mechanism linking risk allele presence with intervention failure has yet to be determined.…”
Section: Discussionmentioning
confidence: 99%